Magnetic ordering and interactions in iron-filled carbon foam. (June 2019) - Boi, F.S.; Zhang, X.; Odunmbaku, O.; Xia, J.C.; Taallah, A.; Baxendale, M.
Abstract: Ferromagnetically filled graphitic-carbon foams are a new class of materials characterized by an open-cell structure continuously filled with ferromagnetic crystals. Targeted design for applications requires knowledge of the magnetic ordering and the interaction between magnetic moments in the filling and those due to the spin of the delocalized π-electrons which contribute to thermal and electrical conduction in the graphitic carbon. Magnetometry together with electron spin resonance, thermoelectric, and calorimetric measurements on iron-filled carbon foam reveal ferromagnetic responses at room temperature with a transition to antiferromagnetic behavior in some fraction of the filling at 130 K. This observation is consistent with the α-Fe (bcc) to γ-Fe (fcc) transition at this temperature predicted by others. Seebeck coefficient measurements revealed a behavior typical of unmodified graphitic carbon indicating the absence of any interaction between the magnetic moments of the filling and the conduction electrons in the graphitic carbon. Highlights: Ferromagnetically filled graphitic-carbon foams are a new class of materials. Magnetometry, EPR, thermoelectric, and calorimetric mesurements were performed. Ferromagnetic responses at room temperature with a transition to antiferromagnetic behaviour are shown. This observation is consistent with the alpha-Fe (bcc) to gamma-Fe (fcc) transition. Seebeck measurements revealed absence of interaction between Fe magnetic moments and the conduction electrons in the foam.